Handbike for Daily Use, Sport, and Rehabilitation Purposes: A Literature Review of Actuation and Technical Characteristics - Michele Sanguinetta; Giovanni Incerti; Cinzia Amici; Giovanni Legnani (Actuators, 2024)
With respect to alternative devices like traditional wheelchairs, handbikes can offer advantages from biomechanical and physiological perspectives, to several kinds of users. Assuring high mechanical efficiency and homogeneous force distributions along cycles, and being suitable for indoor and outdoor activities, these systems are used for rehabilitation, sports, and daily applications. From a technical perspective, their main characteristics can vary with the device final purpose and operational context. This review aims to provide an overall outline of handbikes in the literature from a general and comprehensive point of view, up until 2022. The analysis is performed (i) with a systematic approach, without a priori limitations on document type and content focus, and (ii) to identify the areas of interest for the scientific development of these systems. A systematic evaluation method for the identification and analysis of the documents was designed and implemented and the selection criteria, as well as the rationale for the procedure, are described. A specific taxonomy was defined and applied for the subsequent analysis, and each category is specifically evaluated and described, detailing the main outcomes of the literature analysis and relative discussion. Particular attention is paid to actuation strategies and propulsion efficiency. Finally, the main results of the work and future developments for handbikes are briefly synthesized.